A Rechargeable K/Br Battery. (10th July 2022) - Xia, Maoting; Feng, Yanhong; Wei, Jumeng; Rao, Apparao M.; Zhou, Jiang; Lu, Bingan
Abstract: The current limited and uneven distribution of lithium resources has stimulated strong motivation to develop new rechargeable batteries that use alternative charge carriers. Potassium‐based batteries are promising candidates for future large‐scale energy storage due to their low cost and high operating voltage. Here for the first time, a rechargeable K/Br battery is reported, which is assembled with a hollow carbon spheres cathode, a K metal anode, and a SOBr2 electrolyte containing AlBr3 and potassium bis‐(fluorosulfonyl)imide. The in situ formed crystalline KBr protective film during discharging plays a significant role in this system. The redox reaction between the KBr film and liquid Br2 at the cathode contributes to the main reversible capacity. K/Br battery exhibits high capacity (up to 400 mAh g ‐1 ) and constant operating voltage (at 3.72 V vs K + /K). As a proof of concept, the K/Br battery demonstrated in this work points to a new pathway for low‐cost and next‐generation rechargeable batteries. Abstract : A novel rechargeable K/Br battery is demonstrated for the first time in this work, which exhibits high capacity (up to 400 mAh g −1 ) and constant operating voltage (at 3.72 V vs K + /K). As a proof of concept, the proposed K/Br battery points to a new pathway for next‐generation rechargeable batteries.